Comment mobiliser les jeunes adhérents dans la gouvernance des coopératives agricoles ? - Hichem Amichi; Marie-Christine Henninger; Céline Peltier (Développement Durable et Territoires)
This article analyzes the process of mobilizing a group of young members and employees within an agricultural cooperative located in the southwest of France. This analysis is part of a strategic reflection launched by the cooperative, concerned by the governance issues and questioned by the place that youth can play in the construction of its future strategy. This reflection is initiated in a context where cooperative structures are becoming more complex leading to distancing links with their members especially. This article presents a concrete implementation of an approach aimed to develop the mobilization of members and employees in this cooperative. Such doing, it aims to operationalize the results of the existing scientific literature by proposing the gradual construction of an implementation methodology. As a first step, our approach is based on a qualitative analysis through the realization of several participatory workshops dedicated to a small group of young members and employees followed for a whole year. This work highlights the failure in the environment of mobilization within the cooperative, a widespread situation that is found in many companies faced to governance issues. This article also shows that it is possible to rebuild a sense of mobilization through participatory workshops. This feeling of being able to act, or psychological empowerment, driven by this participatory approach, is a first step towards creating an environment more favorable to collective mobilization. Thus, this article marks a first milestone in terms of a support approach that offers cooperatives avenues and levers of concrete actions to improve their governance.